Participation of calcium-permeable AMPA receptors in the regulation of epileptiform activity of hippocampal neurons - Zinchenko, Valery Petrovich; Teplov, Ilia Yu.; Kosenkov, Artem Mikhailovich; Gaidin, Sergei Gennadievich; Kairat, Bakytzhan Kairatuly; Tuleukhanov, Sultan Tuleukhanovich (Frontiers in Synaptic Neuroscience, 2024)
Introduction Epileptiform activity is the most striking result of hyperexcitation of a group of neurons that can occur in different brain regions and then spread to other sites. Later it was shown that these rhythms have a cellular correlate in vitro called paroxysmal depolarization shift (PDS). In 13–15 DIV neuron-glial cell culture, inhibition of the GABA(A) receptors induces bursts of action potential in the form of clasters PDS and oscillations of intracellular Ca2+ concentration ([Ca2+]i). We demonstrate that GABAergic neurons expressing calcium-permeable AMPA receptors (CP-AMPARs) as well as Kv7-type potassium channels regulate hippocampal glutamatergic neurons’ excitability during epileptiform activity in culture. Methods A combination of whole-cell patch-clamp in current clamp mode and calcium imaging microscopy was used to simultaneously register membrane potential and [Ca2+]i level. To identify GABAergic cell cultures were fixed and stained with antibodies against glutamate decarboxylase GAD 65/67 and neuron-specific enolase (NSE) after vital [Ca2+]i imaging. Results and discussion It was shown that CP-AMPARs are involved in the regulation of the PDS clusters and [Ca2+]i pulses accompanied them. Activation of CP-AMPARs of GABAergic neurons is thought to cause the release of GABA, which activates the GABA(B) receptors of other GABAergic interneurons. It is assumed that activation of these GABA(B) receptors leads to the release of beta-gamma subunits of Gi protein, which activate potassium channels, resulting in hyperpolarization and inhibition of these interneurons. The latter causes disinhibition of glutamatergic neurons, the targets of these interneurons. In turn, the CP-AMPAR antagonist, NASPM, has the opposite effect. Measurement of membrane potential in GABAergic neurons by the patch-clamp method in whole-cell configuration demonstrated that NASPM suppresses hyperpolarization in clusters and individual PDSs. It is believed that Kv7-type potassium channels are involved in the control of hyperpolarization during epileptiform activity. The blocker of Kv7 channels, XE 991, mimicked the effect of the CP-AMPARs antagonist on PDS clusters. Both drugs increased the duration of the PDS cluster. In turn, the Kv7 activator, retigabine, decreased the duration of the PDS cluster and Ca2+ pulse. In addition, retigabine led to deep posthyperpolarization at the end of the PDS cluster. The Kv7 channel is believed to be involved in the formation of PDS, as the channel blocker reduced the rate of hyperpolarization in the PDS almost three times. Thus, GABAergic neurons expressing CP-AMPARs, regulate the membrane potential of innervated glutamatergic neurons by modulating the activity of postsynaptic potassium channels of other GABAergic neurons.